Biotransformación de biomasa foliar de Gmelina arborea Roxb. (Melina) mediante el uso de hongos y bacterias. - Pacheco Merizalde, Carlos Mauricio (2007)
The present investigation had a time of duration of 203 days. The objectives were: To determine the quantity of fertilizer organic in each one of the studied treatments, to determine the levels of N, P, K, Ca and Mg in each one of the utilized treatments and to determine the efficiency of the mushrooms and bacterias for treatment. The utilized treatments were: T1 in the dose of 5 cm3 of Bacton, T2 with 10 cm3, T3 with 15 cm3 and T4 with 20 cm3 all these unthickened ones in 1 liter of water. A Totally at Random Design was used, with four treatments and four repetitions. The experimental units were beds of decomposition, of 1 m x 1m and 25 cm of high with a volume of 0.25 m3. In each experimental unit 10 Kg was of material to foliate of Melina. The Process was evaluated of Biotransformation of Biomass to foliate of Melina by means of the use of mushrooms and bacterias. The valued variables were: I weigh of fertilizer organic by each treatment, levels of N, P, K, Ca and Mg, temperature and the time of decomposition of the material to foliate. The maximum temperature used by the microorganisms was of 27.5 ºC and its minimal temperature in the phase of cooling of 22.3 ºC. No took place significant statistical differences in the production of fertilizer organic. The treatments that produced Nitrogen in levels means were the T1R3, T3R1, T3R3 and T4R1 and the treatment that it produced levels of Nitrogen and higher Calcium was the T4. The remaining treatments had similar levels of Match, Potassium and Magnesium. It was determined that the levels of nutritious product of the process of biotransformation, they were statistically same.